Kunstfaggruppens infrastrukturelle aktivisme: En feministisk læsning af kunstbibliotekarernes arbejde i 1970’erne - Ellegaard, Line (Passage - Tidsskrift for litteratur og kritik, 2025)
“The Infrastructural Activism of Kunstfaggruppen: A Feminist Reading of Art Librarians’ Work in the 1970s” This article explores the art librarians in Kunstfaggruppen’s (the Art Subject Group’s) infrastructure-creating and agenda-setting activities, situated at the inter- section between visual arts and the library system. During the 1970s the group, dominated by women informed by feminism, ensured that art libraries became a recognised part of the art institutional landscape in Denmark. This article argues that this happened through a form of “infrastructural activism” (Smith). Seeking to create an alternative to the bourgeois art institution, this activism operates on both infrastructural and representational levels within the frameworks of art. The ar- ticle suggests that the infrastructural and activist work thatdrove Kunstfaggruppen in the 1970s had a feminist impulse, but also critically considers the relationship between the counterculture of the women’s movement and the cultural politics of the welfare state, whilst reflecting on the potential of the art library infrastructure today.